Carex talbotii (Cyperaceae), a replacement name for Berggren’s Sedge - Kottaimuthu, Ramalingam; Basu, Muthuramalingam Jothi (Phytotaxa, 2020)
Carex Linnaeus (1753: 972) is one of the largest genera of angiosperms with about 2000 species (Jiménez-Mejías et al. 2016a). According to the Global Carex Group (2015) circumscription, it is nearly a cosmopolitan genus with higher species diversity in cold-temperate areas of the Northern Hemisphere (Martín-Bravo et al. 2019). A recent revision of Carex fossils (Jiménez-Mejías et al. 2016b) provided an exhaustive compilation of Carex names coined for fossils, later compiled by IFPNI (2014–present). Some cases of the homonymy between extant and fossil species have been recently resolved by Turner (2014, 2015), Doweld (2015, 2016a–b, 2017a–c, 2018), Kottaimuthu (2017, 2018a–b, 2019) and Govaerts (2018). During routine nomenclatural check for the existence of the homonymy between extant and extinct members of sedges, we identified that the Berggren’s sedge namely Carex berggrenii Petrie (1886: 297) is illegitimate because there exists an earlier homonym Carex berggrenii Heer (1870: 49) a fossil-species described from Spitsbergen island (Svalbard archipelago, Norway). Since no legitimate synonyms are available for this endemic sedge (Hamlin 1968, Edgar 1970, Breitwieser & Wilton 2020, Govaerts et al. 2020, POWO 2020), the replacement name Carex talbotii Kottaim. is proposed here.